Evaluación de la calidad de las guías de práctica clínica utilizadas en la rehabilitación del accidente cerebrovascular - Maldonado-Borja, Diana (2018)
Context: clinical practice guidelines (CPG) provide systematic recommendations to facilitate decision making based on the best scientific evidence.Objective: to evaluate the quality of clinical practice guidelines related to stroke rehabilitation (CVA).Methods: an online CPG search was conducted on ACV rehabilitation based on the AGREE II instrument that guarantees academic quality; being a computer tool, it values methodological rigor and transparency in the development of CPGs.Results: through search engines, 63 guidelines were selected for evaluation, discarding documents in the Anglo-Saxon language (n = 13) and non-technical documents (n = 29) - After the first screening, 18 additional guides were eliminated due to not being subject to the inclusion criteria: a) Spanish language, b) year of publication between January 2012 to March 2017, c) full text, d) free access to full text and e) related to the rehabilitation of the ACV. Only three guides met all the inclusion criteria. The results of AGREE II varied widely among the different domains, with the highest score being given to a guide that met 60% of each of the six domains assessed.Conclusion: there is variability in the quality of the evaluated guides; the guide published by the Ministry of Health and Social Protection COLCIENCIA of Colombia was selected for methodological quality. Increased rigor at the time of developing management guides, under writing parameters, methodology and scientific evidence.